Yowamushi pedal. 14 - Watanabe, Wataru, 1971- (Yen Press, 2020)
"Only 500 meters remain! Manami Sangaku of Hakone Academy and Onoda Sakamichi of Sohoku High are neck-and-neck on the final stretch! Will the reigning champs keep their crown, or will Sohoku take the trophy!?"--Provided by publisher.